DEVELOPMENT OF PROBLEM-SOLVING SKILLS TEST ON DYNAMIC FLUID MATERIAL AT SMA TARUNA PBD MEDAN - Putri Lindon Sihombing; Abubakar (Journal of Learning and Technology in Physics, 2024)
This study focuses on the development of a physics problem-solving skills test instrument on dynamic fluid material for grade XI high school students. The purpose of this study is to determine how to develop a problem-solving-based test instrument on dynamic fluid material and to determine the feasibility of a problem-solving-based test instrument on dynamic fluid material. The type of research used in this study is R & D (Research and Development) development research using the ADDIE research model which has a research design through four stages, namely Analysis, Design, Development, Implementation and Evaluation. The trial sample in this study was 29 grade XI students of Taruna PBD Medan High School with the assumption that the entire class is homogeneous. The research instrument used is a problem-solving skills test consisting of 7 questions in the form of essays. The trial results were obtained from the problem-solving ability test instrument in the validation test conducted by 3 validators who had a very high value category which was included in the category of suitable for use with revision. Analysis of the problem-solving ability instrument administered to 29 students, with the results obtained in the validity and reliability trials, showed that all test instruments were valid and reliable. In the trial, the difficulty level of five questions was classified as moderate, one was classified as easy, and one was classified as difficult. Furthermore, in the discrimination test, the seventh question was categorized as excellent. Thus, the developed test instrument was suitable for use with five questions. So it can be concluded that the development of instruments based on students' problem-solving abilities is suitable for measuring students' thinking abilities. Keywords:Test instrument, Problem Solving skills